2014
DOI: 10.1007/s00262-014-1639-3
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-induced myeloid dysfunction and its implications for cancer immunotherapy

Abstract: Immune function relies on an appropriate balance of the lymphoid and myeloid responses. In the case of neoplasia, this balance is readily perturbed by the dramatic expansion of immature or dysfunctional myeloid cells accompanied by a reciprocal decline in the quantity/quality of the lymphoid response. In this review, we seek to: 1) define the nature of the atypical myelopoiesis observed in cancer patients and the impact of this perturbation on clinical outcomes; 2) examine the potential mechanisms underlying t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
91
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(94 citation statements)
references
References 124 publications
2
91
1
Order By: Relevance
“…Ample evidence supports a close association between MDSC accumulation and clinical outcome in cancer patients (91). Most solid tumors have expansion of PMN-MDSCs, with some exceptions, including melanoma, multiple myeloma, and prostate cancer.…”
Section: Mdscs As Biomarker Of Tumor Progression and Responsiveness Tmentioning
confidence: 99%
“…Ample evidence supports a close association between MDSC accumulation and clinical outcome in cancer patients (91). Most solid tumors have expansion of PMN-MDSCs, with some exceptions, including melanoma, multiple myeloma, and prostate cancer.…”
Section: Mdscs As Biomarker Of Tumor Progression and Responsiveness Tmentioning
confidence: 99%
“…MDSC expansion and mobilization is now a hallmark of cancer (Cuenca, et al, 2014;Messmer, et al, 2015). In patients with PC, the leukocyte fraction of circulating MDSCs is elevated and further increases with disease progression (Markowitz, et al, 2015;Porembka, et al, 2012).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The use of aberrant myelopoiesis as a biomarker and prognostic indicator for tumor progression has been however hampered by the wide range of markers that have been used to define these cells as mentioned by Messmer et al [44]. Despite this, several studies have convincingly shown the relation between the accumulation of immunosuppressive myeloid cells and tumor progression in a range of tumor types [41-43, 45-47, 50, 100, 101].…”
Section: Origin and Subtypes Of Mdscsmentioning
confidence: 99%
“…MDSCs isolated from melanoma, glioma, squamous cell carcinoma, non-small cell lung cancer, breast cancer, hepatocellular carcinoma, gastric cancer, colorectal and chronic myeloid leukemia cancer patients have been shown to suppress antigen-specific and CD3-ligation induced T cell proliferation [29, 30, 42, 45, 103]. MDSC expansion has been negatively associated with tumor stage, metastatic burden, response to therapy and progression-free or overall survival [44, 46, 47, 104, 105] .…”
Section: Origin and Subtypes Of Mdscsmentioning
confidence: 99%
See 1 more Smart Citation